Creating Well-Structured Specifications in MOFLON - Amelunxen, Carsten; Rötschke, Tobias (Electronic Communications of the EASST, 2007)
Considering the growing popularity of model-based development, specificationsbecome more complex. As a consequence, graph-based modeling toolshave to take measures to handle this complexity. In this paper, we present the metamodelingenvironment MOFLON which has been developed on top of the FUJABAToolsuite during the last few years at our department. We focus one of MOFLON'sstrongest advantages, i.e. the realization of the abstraction and modularization featuresintroduced by the recent UML 2.0 Infrastructure specification. The new conceptof package merge allows to reuse and refine existing models without modifyingthe original. Subset and redefinition relationships become useful tools to refine associationsdue to the automatic propagation mechanism generated by the MOFLONcode generator. We show how the user can organize large specifications using theseconcepts and how they effect graph transformation rules and code generation.